2017
DOI: 10.1161/jaha.117.006545
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Smoking and Serum GlycA and High‐Sensitivity C‐Reactive Protein Levels: The Multi‐Ethnic Study of Atherosclerosis (MESA) and Brazilian Longitudinal Study of Adult Health (ELSA‐Brasil)

Abstract: BackgroundInflammation is suggested to be a central feature of atherosclerosis, particularly among smokers. We studied whether inflammatory biomarkers GlycA and high‐sensitivity C‐reactive protein are associated with cigarette smoking.Methods and ResultsA total of 11 509 participants, 6774 from the MESA (Multi‐Ethnic Study of Atherosclerosis) and 4735 from ELSA‐Brasil (The Brazilian Longitudinal Study of Adult Health) were included. We evaluated the cross‐sectional association between multiple measures of smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Our data suggested that smokers in the third hs-CRP quartile had increased chance of getting CVDs. This was consistent with other studies demonstrated a positive correlation between smoking and hs-CRP levels [27,28]. Results of Hung et al [28] study showed that in comparison with non-smokers, anyone who smokes in middle or high levels of hs-CRP had increased odds of coronary vasospasm and this finding suggested that smokers developed vasospasm at lower hs-CRP levels.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data suggested that smokers in the third hs-CRP quartile had increased chance of getting CVDs. This was consistent with other studies demonstrated a positive correlation between smoking and hs-CRP levels [27,28]. Results of Hung et al [28] study showed that in comparison with non-smokers, anyone who smokes in middle or high levels of hs-CRP had increased odds of coronary vasospasm and this finding suggested that smokers developed vasospasm at lower hs-CRP levels.…”
Section: Discussionsupporting
confidence: 89%
“…Results of Hung et al [28] study showed that in comparison with non-smokers, anyone who smokes in middle or high levels of hs-CRP had increased odds of coronary vasospasm and this finding suggested that smokers developed vasospasm at lower hs-CRP levels. Another cross-sectional study revealed that all aspects of smoking habits had significant association with hs-CRP biomarker [27]. Since it was proved that hs-CRP levels would be increased in smokers, several health care strategies should be done to decrease the prevalence of smoking in order to decline these two independent cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Kianoush et al studied the association between smoking and systemic inflammation (GlycA) in 11,509 participants from MESA and 'The Brazilian Longitudinal Study of Adult Health' (ELSA-Brasil) cohorts. They found similar significant associations between different measures of smoking behavior and higher GlycA and hsCRP levels [134].…”
Section: Treatment Effects and Lifestyle Tobacco Smokingmentioning
confidence: 73%
“…Smokers who were still smoking at the time of the interview were considered as current smokers, and those who had quit (for at least 30 days before the interview) were former smokers. 26 Pack-years were calculated in smokers by multiplying the average number of cigarettes smoked per day by the number of years of smoking and by dividing by 20 cigarettes/pack. Participants were classified as follows: 0, 0–20 and >20 pack-years.…”
Section: Methodsmentioning
confidence: 99%